2016
DOI: 10.1007/s40890-016-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Driving Behaviors: Models and Challenges for Non-Lane Based Mixed Traffic

Abstract: Most published microscopic driving behavior models, such as car following and lane changing, were developed for homogeneous and lane-based settings. In the emerging and developing world, traffic is characterized by a wide mix of vehicle types (e.g., motorized and non-motorized, two, three and four wheelers) that differ substantially in their dimensions, performance capabilities and driver behavior and by a lack of lane discipline. This paper presents a review of current driving behavior models in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…is driving behaviour in mixed traffic stream can be analysed by empirical data collection from real-time traffic data. A very limited data on vehicle trajectory are available in case of mixed traffic due to high cost and difficulty in data collection and its extraction and huge variations in vehicle type, size, and dynamics [125].…”
Section: Driver Behavioural Data In Mixed Trafficmentioning
confidence: 99%
“…is driving behaviour in mixed traffic stream can be analysed by empirical data collection from real-time traffic data. A very limited data on vehicle trajectory are available in case of mixed traffic due to high cost and difficulty in data collection and its extraction and huge variations in vehicle type, size, and dynamics [125].…”
Section: Driver Behavioural Data In Mixed Trafficmentioning
confidence: 99%
“…Asaithambi et al [5] have reviewed driver behavior models under mixed traffic conditions and have pointed out limitations of current models, arguing that the main limitation is that they do not explicitly consider the wider range of situations that drivers in mixed traffic face. Munigety and Mathew [2] have identified that due to weak lane discipline, drivers maneuvering in mixed traffic streams exhibit some peculiar patterns such as maintaining shorter headways, swerving, and filtering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, more than 2000 cyclists and 7000 pedestrians were killed annually in the European Union, accounted for 27% of all fatalities [1]. The situation was even worse in the emerging and developing countries like India and China [2]. Their rapid economic growths increase travel demand, but overwhelm the limited transportation infrastructure.…”
Section: Introductionmentioning
confidence: 99%